Characteristics of milk fever and mastitis following different milking method and preventive calcium injection performed during the colostrum period in dairy cattle - Ryounghoon Jeon (The Korean Society of Animal Reproduction and Biotechnology, 2020)
The milk fever and mastitis that occur during the colostrum period in dairy cattle cause great damage in the dairy industry by causing a rapid decline in the cattle's health and decreasing milk production. In order to prevent this, gradual milking (GM), calcium injection with gradual milking (CG), and calcium injection with complete milking (CC) methods are used. However, differences in effectiveness between these methods have not been established. Therefore, this study was conducted to determine the effects of each preventive method on milk fever and mastitis. The results of this study showed that while there was a significant negative correlation of GM with milk fever and mastitis (r = -0.657, p < 0.05), there was no correlation of CG and CC with milk fever and mastitis. The incidence of milk fever was significantly lower in CG and CC than in GM (p < 0.05) but no differences in the incidence of mastitis were observed between the three groups. No significant differences in the rate of recovery from milk fever and mastitis were observed between the three groups. The recurrence rate of milk fever was significantly higher in CG and CC than in GM (p < 0.05), though no differences in the recurrence rate of mastitis were observed. This study showed an inverse relationship between the incidence rates of milk fever and mastitis when calcium injection was not used during the colostrum period. When calcium injections were used, the incidence of milk fever was reduced without affecting the incidence of mastitis regardless of the milking method, but the recurrence rate of milk fever was increased. The results of this study would be useful for controlling blood calcium concentrations and establishing efficient milking strategy in order to effectively prevent milk fever and mastitis in dairy cattle during the colostrum period.